Cyclic behavior of natural organic clay under variable confining pressure that match traffic loading conditions. Issue 3 (16th March 2019) - Wang, Yuke; Zeng, Changnv; Jia, Heyang; Cai, Hongjian; Zhang, Xiangyuan
ABSTRACT: One-way cyclic loading is more typical for traffic loading and cyclic triaxial test has been recognized as a useful method for solving many engineering problems. Under traffic loading, the influence of variable confining pressure on cyclic behavior of natural organic clay subjected to cyclic traffic loading is rarely reported in the literature. In this study, a laboratory investigation on undrained cyclic behavior of natural organic clay is presented and conducted by cyclic triaxial apparatus. Tests are conducted by both constant confining pressure and variable confining pressure, to simulate the loading conditions induced by passing vehicles in actual engineering. Different stress levels are also considered in this study. By comparing between the results of constant confining pressure tests and variable confining pressure tests, it shows that the one-way cyclic behavior of organic clay is influenced significantly by variation of confining pressure, in terms of pore water pressure, permanent axial strain and stress–strain hysteretic loops.